Implementation Rationality: The Nexus of Psychology and Economics at the RAND Logistics Systems Laboratory, 1956-1966 - Judy L. Klein (Duke University, Center for the History of Political Economy (CHOPE), 2015)
In October 1956, the RAND Corporation establis hed the Logistics Systems Laboratory (LSL) with the goal of using simulation to translate the broad findings of normative microeconomics into detailed, implementable pr ocedures for US Air Force oper ations. The laboratory was housed in the training simulation facilities that had been recently vacated by psychologists working at the RAND Systems Research Laboratory. Economists at the LSL, interwove their marginal cost- benefit analysis with the psychologists' focus on process, adaptation, a nd group behavior. Over the course of a decade, economists and psycholog ists at the RAND Logistics Systems Laboratory conducted game simulations structured by the f our separate laboratory problems. Economists went from using simulation to demonstrate the superiority of optimal policies derived from deductive economics to using the ex periment as an inductive tool. One of the concerns in this historical case study is with how economics leveraged psychology to grow a regulatory system when individual units pursuing their own interest s did not promote effect ually the interests of society. This dilemma was one of a few stimuli ge nerating a new focal point for rationality, that of efficient implementation. More recently, economists on the BIS Basel Committee on Banking Supervision were engaging in implementation ra tionality through simulation in the form of the Regulatory Consistency Assessment Programme ( RCAP). The examination of iterative modeling and solving for rules of action at the LSL and in the RCAP suggest that the explicit narrowing of modeling choices that bind the ratio nality of the individual units w ould be best iterated through a process that takes into account the human factor. Interactions with experimental psychologists opened a door for economists to non-standard mode ling and an iterative, he uristic specification of economizing rules of action that ha d a greater chance of implementation.
Keywords: B21; C6; C92; B4; D03; D61; G28; 330; normative microeconomics; cost-benefit anal ysis; procedural rationality; implementation rationality; systems analysis; simulati on; experiments; regulation; history of economics; Murray Geisler; RAND Logistics Systems Laboratory; RAND Systems Research Laboratory